Teatro de se ler : o texto teatral e a formação do leitor - Grazioli, Fabiano Tadeu (2007)
In face of lots of verifications about non-reading Brazilian students , we can point out the negligence of the school and the teachers with the reading of the written theatrical text. The dramatic genre doesn t find, in the actual moment, a large place, where it can be received to its reading and where it can be the target of discussion and debates about the language that characterize it and about the art projecting by him, about the contents it points and about the effects it provokes in the first-time readers reception. Such evidence is the starting point of this investigative work, which gives credit to the theatrical text reading to the hard and urgent task of the readers formation and to insert, in a significant way, the dramatic activity in the scholar context. In the first chapter, we show a view of the theater in the school, focusing the general principles of this art in the scholar context, the dramatic approaching, which reveal the theater presence in the Brazilian school and the reasons of the significant theatrical activity removal, involved and engaged with principles showed previously. In the second chapter, we will treat the existent relation between the literary theory that involved the dramatic genre and this genre reading. Our reflections are pointed by two aspects: the theoretical considerations, which make the dramatic genre reading impracticable, and that ones which point the reception of that referred genre as satisfactory and complete starting from the written text reading, focusing two theoretical points around the theatrical text: its nature and its composition or structure. The literary reading is thematized and discussed in the third chapter. We starting point from the Judith Langer studies, in conversation with the others authors and we present the most important aspects around the literary experience, highlighting, in the chapter closing, to the teacher role in the literary reading promotion and in the readers formation. In the last chapter we created a work plan for the Ensino Fundamental and Médio (Elementary, Middle, and High School), starting from the theatrical text, moment in which we will develop reading practices, based on the theoretical notes, showed in the previous chapters. The texts utilized in the activities are A Caravana da ilusão, from Alcione Araújo and Dous or O Inglês Maquinista, from Martins Pena, both belonged to the anthology Dramaturgia de Sempre, from Editora Civilização Brasileira